A novel GaN vertical junction field-effect transistor with intrinsic reverse conduction capability and kilo-volt breakdown voltage. (22nd December 2020) - Chen, Kuangli; Zhou, Qi; Zhu, Liyang; Dong, Zhiwen; Huang, Peng; Deng, Chao; Cai, Yonglian; Gao, Wei; Zhou, Chunhua; Chen, Wanjun; Zhang, Bo
Abstract: In this work, a novel GaN vertical junction field-effect transistor (JFET) with intrinsic reverse conduction capability (RC-JFET) is proposed and studied by simulation. The RC-JFET features two separate source electrodes, one of which performs as an embedded freewheeling diode that can enable the reverse conduction function of the device. Benefiting from a structure with two separate source electrodes, the forward and reverse current conduction paths are also separated, which allows us to independently design the forward and reverse conduction characteristics of the RC-JFET. The forward threshold voltage V TH is 1.6 V while the reverse turn-on voltage V on, rev is as low as 0.7 V. In addition, the buried floating p-base can effectively modulate the E-field in the GaN drift region, which can achieve a high breakdown voltage of 1720 V with an R on, sp of 2.79 mΩ cm 2 . Due to the embedded freewheeling diode, the device exhibits a short reverse recovery time T rr of 13 ns. By featuring an intrinsic reverse conduction capability, the proposed RC-JFET is capable of eliminating the externally connected diode, which is beneficial for improved switching speed and switching power loss due to the reduction of parasitic effects and chip size of power circuits.